2006
DOI: 10.1002/cne.21207
|View full text |Cite
|
Sign up to set email alerts
|

Selective loss of dentate hilar interneurons contributes to reduced synaptic inhibition of granule cells in an electrical stimulation‐based animal model of temporal lobe epilepsy

Abstract: Neuropeptide-containing hippocampal interneurons and dentate granule cell inhibition were investigated at different periods following electrical stimulation-induced, self-sustaining status epilepticus (SE) in rats. Immunohistochemistry for somatostatin (SOM), neuropeptide Y (NPY), parvalbumin (PV), cholecystokinin (CCK), and Fluoro-Jade B was performed on sections from hippocampus contralateral to the stimulated side and studied by confocal laser scanning microscopy. Compared to paired age-matched control anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
114
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 66 publications
13
114
2
Order By: Relevance
“…In addition, NPY increases in the hippocampus in KA-induced seizures, which suggests that the NPY-positive neurons are resistant to KA-induced seizures in the whole hippocampus, but NPY/NADPH-d-positive neurons have different sensitivities in its subregions [53] . This is contradictory to previous research [43,51] , and may be due to the different models and However, PV-positive interneurons are highly susceptible to acute seizure activity in both age groups [54] . Moreover, there are much greater decreases in the NPY-and PVpositive interneurons in the hippocampus of aged rats after seizures.…”
Section: Neuropeptide-containing Interneurons and Epilepsycontrasting
confidence: 91%
See 3 more Smart Citations
“…In addition, NPY increases in the hippocampus in KA-induced seizures, which suggests that the NPY-positive neurons are resistant to KA-induced seizures in the whole hippocampus, but NPY/NADPH-d-positive neurons have different sensitivities in its subregions [53] . This is contradictory to previous research [43,51] , and may be due to the different models and However, PV-positive interneurons are highly susceptible to acute seizure activity in both age groups [54] . Moreover, there are much greater decreases in the NPY-and PVpositive interneurons in the hippocampus of aged rats after seizures.…”
Section: Neuropeptide-containing Interneurons and Epilepsycontrasting
confidence: 91%
“…This is mainly because aging alone can substantially depletes these populations. In addition, NPY-IR interneurons are evidently lost in the hilus of the dentate gyrus but preserved in the granule cell layer in electrical stimulation-induced epilepsy [51] . Similar losses of NPY-IR interneurons have been reported in KA models [55] .…”
Section: Neuropeptide-containing Interneurons and Epilepsymentioning
confidence: 98%
See 2 more Smart Citations
“…We found that scAAV5-GABRA4-TREK-M pre injected rats had significantly less fig 8F). However, no reduction was observed in FJC+ cells in the dentate gyrus, where neuronal death predominantly occurs in the hilus as others have observed previously (Wang, Ghosh et al 2008;Sun, Mtchedlishvili et al 2007). In order to quantify the number of dead cells which is represented by green colored FluoroJade -C stained neurons, we calculated the Fluoro-Jade C positive neurons in each brain slice.…”
Section: Trek-m Protected Against Neuronal Deathsupporting
confidence: 62%